2006
DOI: 10.3390/curroncol13020003
|View full text |Cite
|
Sign up to set email alerts
|

The Do-Not-Resuscitate Order: Incidence of Documentation in the Medical Records of Cancer Patients Referred for Palliative Radiotherapy

Abstract: Patients with symptomatic metastases referred for outpatient palliative radiotherapy for symptom control at the Rapid Response Radiotherapy Program (rrrp) and the Bone Metastases Clinic (bmc) at the Toronto–Sunnybrook Regional Cancer Centre have a limited life expectancy. Relevant medical information is missing from the files of many referred patients when they arrive at the clinics, potentially causing delayed treatment and ambiguity in the best management of their needs in situations of worsening condition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…We observed a rate of GoC designation documentation comparable with other retrospective studies in patients with advanced cancer, 6,7,10,13,14,16,17 which reported rates as low as 6% and as high as 80%. The two studies with the highest overall rates of documentation (73% and 80%) noted that the majority of conversations happened when patients were admitted to hospital.…”
Section: Discussionsupporting
confidence: 88%
“…We observed a rate of GoC designation documentation comparable with other retrospective studies in patients with advanced cancer, 6,7,10,13,14,16,17 which reported rates as low as 6% and as high as 80%. The two studies with the highest overall rates of documentation (73% and 80%) noted that the majority of conversations happened when patients were admitted to hospital.…”
Section: Discussionsupporting
confidence: 88%
“…2,3 ASCO and the National Cancer Comprehensive Network recommend that these patients also be considered for early referral to palliative care (PC) 3,4 . Despite these guidelines, studies have shown that the rates of GOC documentation [5][6][7] and PC referral 8,9 are low in many institutions. A recent audit of patients with metastatic lung, pancreatic, colon, and breast cancer receiving palliative chemotherapy at the Cancer Centre of Southeastern Ontario (CCSEO) between 2010 and 2015 revealed that only 6% of patients had a documented GOC discussion and only 47% of patients had been referred to PC.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Overall, the 72% prevalence of high-quality GoC discussions reported by patients was higher than we expected and has been reported in the literature. [21][22][23] Shockingly, despite wide differences in patient, oncologist, and hospital characteristics as well as productivity across sites, productivity did not change whether high-quality GoC discussions did or did not take place. Moreover, no difference in the prevalence of high-quality GoC discussions was found between the intervention and usual care group oncologists, despite a more intense training intervention oncologists received in conducting GoC discussions.…”
Section: Discussionmentioning
confidence: 97%